2023
DOI: 10.1136/bmjopen-2022-067987
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of over-the-counter and prescription medication during pregnancy in the UK: findings from survey free-text responses and narrative interviews

Abstract: ObjectivesTo explore women’s experiences of over-the-counter and prescription medication advice and use during pregnancy.DesignA study design consisting of an online survey and nested in-depth interviews with a subsample of participants. We analysed data from survey free-text responses and in-depth interviews using thematic analysis. Quantitative survey data is published elsewhere.SettingThe UK.ParticipantsWomen were eligible if living in the UK, aged 16–45 years, were pregnant or had been pregnant in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A qualitative study of women’s experiences of antenatal medication use in the United Kingdom found that many pregnant women wished to reduce exposure to OTC and prescribed medications, but dietary supplements and vaccines were generally accepted. 15 Almost all women in our study reported that not all OTC medications are safe to use during pregnancy, yet most used at least one. Some data also suggest that pregnant women’s awareness of the risks associated with use of medication have decreased, and some pregnant women consider medications harmless.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A qualitative study of women’s experiences of antenatal medication use in the United Kingdom found that many pregnant women wished to reduce exposure to OTC and prescribed medications, but dietary supplements and vaccines were generally accepted. 15 Almost all women in our study reported that not all OTC medications are safe to use during pregnancy, yet most used at least one. Some data also suggest that pregnant women’s awareness of the risks associated with use of medication have decreased, and some pregnant women consider medications harmless.…”
Section: Discussionmentioning
confidence: 75%
“… 2 Among pregnant women in the United Kingdom, important themes relating to prenatal medication experiences included a fear of medications and self-regulation, feeling overmedicated, and conflicting opinions. 15 Prenatal OTC medication has been considered a global reproductive health concern. 14 No studies in Canada have assessed OTC medication use in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Risk-benefit consideration are further complicated by poor quality information and conflicting views expressed by health care professionals. It was highlighted in a recent study reporting pregnant women being denied or given negative comments about use of medicine that is needed to manage or prevent serious medical conditions in pregnancy [62]. Information related to medicine use in pregnancy shared via the internet also seemed to increase unjustified anxiety as fears of women are amplified by the global web [63], leading to an increase in concerns about the use of medicines in pregnancy in general.…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies have found that women are keen to discuss medication use in relation to pregnancy with their prescribers, however teratogenic medication counselling is rarely given in primary care nor recorded. (32,33) This is the first UK based review to provide some insight into why prescribers may not be providing such information to their patients; possibly due to suboptimal and contradictory sources of local formulary prescribing advice. Thus, this review provides essential groundwork for further quantitative and qualitative work (already underway by the authors), to better understand the facilitators and barriers to providing such medication counselling in primary care and allow for future intervention development.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…(25)(26)(27) Previous work on other teratogenic medications regularly prescribed in primary care and feedback from women suggests such counselling is not often provided. (32,33) Suggested possible reasons for this suboptimal care include lack of time, opportunity, financial incentive and prescriber knowledge. (34) Primary care prescribers (including GPs and non-medical prescribers) issue most SSRIs in the UK and are guided by the British National Formulary, National Institute for Health and Care Excellence (NICE), royal colleges, and local prescribing formularies.…”
Section: Introductionmentioning
confidence: 99%